Peran Pendidikan Kewarganegaraan dalam Menumbuhkan Kedisiplinan Norma Siswa Sekolah Dasar - Adisel Adisel; Suryati Suryati; Venny Andeska Rahyu; Widiyawati Widiyawati; Melinda Melinda; Mira Deva Tri Juniarti; Ahmad Berli; Jendri Nopran Satria; Anisa Orsidia (IJOCE: Indonesia Journal of Civic Education, 2021)
ABSTRACT The purpose of this study was to determine the role of civic education in fostering discipline norms of elementary school students. With education, it will arise in a person to compete and motivate ourselves to be better in all aspects of life. This study uses a qualitative method approach. The results showed that civic education teaches students about values, norms and morals. By practicing values, norms and morals, it will create a disciplined character in students. The existence of discipline makes the educational process that takes place at school will go well, because students do not violate school rules. The conclusion of this study is that the discipline of norms in elementary school students is really needed, because the discipline of norms is included in the formation of character in children. Keywords: Citizenship Education, Discipline, Student Norms.